Privacy and anonymity in the digital era - Gritzalis, Stefanos (Internet research, 2006)
This e-book discusses the issues surrounding informational privacy - assuming that privacy is the indefeasible right of an individual to control the ways in which personal information is obtained, processed, distributed, shared and used by any other entity. The review of current research work in the area of user privacy has indicated that the path for user privacy protection is through the four basic privacy requirements namely anonymity, pseudonymity, unlinkability and unobservability. By addressing these four basic requirements one aims to minimize the collection of user identifiable data.